Hubungan Antar Faktor Pendorong Keberhasilan Manajemen Proyek TI di Perguruan Tinggi Pemerintah - Sihombing, Boy Sandi Kristian; Teguh Raharjo; Ni Wayan Trisnawaty (AI Society & STMIK Indonesia, 2025)
GS is an Indonesian government higher education institution (GHEI) that uses work productivity (WP) and work discipline (WD) applications to calculate monthly performance. However, GS's monthly performance throughout 2023 was below target. The implementation of business intelligence (BI) was considered the best integration solution for data analysis and visualization for GS management. Given the high cost and risk of implementation, this study focuses on IT project management success factors that include organizational culture, knowledge sharing, and open innovation. Data from 94 respondents were processed using PLS-SEM, resulting in two model scenarios: inbound open innovation positively impacts outbound open innovation in one scenario, and vice versa in the other. This research recommends GS to prioritize organizational culture and knowledge sharing in IT project strategy through open innovation. The research model can be used as a reference for further research due to its 87.5% success rate.